Science Teacher Educators’ Perceptions of Science Education in Indonesia: Challenges, Systemic Barriers, and Pedagogical Gaps - Ikmanda Nugraha; Dian Hendriana (Badan Kebijakan Pendidikan Dasar dan Menengah, Kemendikdasmen, 2026)
Science education in Indonesia continues to grapple with systemic and persistent challenges, particularly regarding teacher quality and the overall effectiveness of science teaching and learning. This study aims to examine Science Teacher Educators’ (STEs) perceptions of the current state of science education in Indonesia, the key challenges affecting its development, as well as the systemic factors influencing teacher preparation and classroom practice. Using a qualitative research design, semi-structured interviews were conducted with 19 STEs from a leading university in science education in Bandung, West Java, Indonesia. The data were analyzed using thematic analysis. The findings reveal that STEs perceived science education in Indonesia as still facing interconnected challenges, including inconsistent teacher professionalism, disparities in the quality of teacher preparation across institutions, limited opportunities for practical and inquiry-based learning, frequent curriculum changes without sustained policy direction, and skepticism toward international assessments. Overall, these findings highlight the complex interplay among institutional, policy, and cultural factors shaping science education in Indonesia and underscore the need to strengthen teacher education as a key strategy to improve the quality of science education.